Endobronchial Ultrasound Transbronchial Needle Aspiration for the Diagnosis of Lymphoma. Issue 2 (April 2018) - Gandotra, Sheetal; Dotson, Travis; Lamar, Zanetta; Bellinger, Christina
Abstract : Background: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) presents a minimally invasive way to evaluate abnormal mediastinal and hilar adenopathy. Although EBUS has been established as an effective modality to diagnose lung cancer, its sensitivity for the diagnosis of lymphoma has been demonstrated to be lower. Because of these lower yields uncertainty persists about the ability of EBUS-TBNA to reliably diagnose lymphoma and questions remain regarding the utility of EBUS-TBNA as a first-line biopsy modality for patients suspected of having lymphoma. Methods: We conducted a review of our database (n=806 EBUS-TBNAs) for patients undergoing EBUS-TBNA for mediastinal and/or hilar lymphadenopathy over an 8-year span to identify patients diagnosed with lymphoma. Results: Twenty patients (2.3%) who underwent EBUS-TBNA were ultimately diagnosed with lymphoma. In total, 17 of the 20 patients with lymphoma obtained a diagnosis using EBUS-TBNA. The overall sensitivity of EBUS-TBNA for lymphoma was 85%. The sensitivity for de novo diagnosis was 78% (7/9), and sensitivity for recurrence was 91% (10/11). All patients who achieved a diagnosis by EBUS-TBNA could be adequately subtyped, allowing treatment recommendations. Conclusion: Although the sensitivity of EBUS-TBNA for the diagnosis of lymphoma did not reach values of published data for non–small cell lung cancer, EBUS-TBNA can be considered as a first-line diagnostic tool for patients with mediastinal and/or hilar lymphadenopathy suspected to be lymphoma. Because of the inherent limitations in small volume needle biopsies it is essential that negative samples obtained in the setting of high clinical suspicion warrant further evaluation.